Peranan Orang Tua dalam Mitigasi Learning Loss di Era Digital - Siregar, Riadi Syafutra; Ghufronuddin; Dwi Astutik; Bagas Narendra; Yuhastina (Ilin Institute, 2022)
The community service program aims to provide parents with an understanding of their role in mitigating learning loss in the digital era, an overview of the digital era, the characteristics, causes, impacts and skills in mitigating learning loss as well as knowledge about effective learning strategies for children. Conducted by outreach to 40 members of the PKK women's group RT 04/RW 06Sawahan Village, Jaten, Karanganyar on July 17, 2022. The implementation of the activities is divided into five stages; Analysis of the problems and needs of parents, initial tests, delivery of material, discussions and questions and answers, and final tests. The results of this socialization program show an increase in parents' understanding and knowledge regarding learning loss mitigation in the digital era and foster the enthusiasm of parents to participate in assisting children so that they are not affected by learning loss and try to apply it in accompanying children's learning activities